Role of glycolysis in inflammatory bowel disease and its associated colorectal cancer - Xia, Yuxuan; Zhang, Li; Ocansey, Dickson Kofi Wiredu; Tu, Qiang; Mao, Fei; Sheng, Xiumei (Frontiers in Endocrinology, 2023)
Inflammatory bowel disease (IBD) has been referred to as the “green cancer,” and its progression to colorectal cancer (CRC) poses a significant challenge for the medical community. A common factor in their development is glycolysis, a crucial metabolic mechanism of living organisms, which is also involved in other diseases. In IBD, glycolysis affects gastrointestinal components such as the intestinal microbiota, mucosal barrier function, and the immune system, including macrophages, dendritic cells, T cells, and neutrophils, while in CRC, it is linked to various pathways, such as phosphatidylinositol-3-kinase (PI3K)/AKT, AMP-activated protein kinase (AMPK), mammalian target of rapamycin (mTOR), and transcription factors such as p53, Hypoxia-inducible factor (HIF), and c-Myc. Thus, a comprehensive study of glycolysis is essential for a better understanding of the pathogenesis and therapeutic targets of both IBD and CRC. This paper reviews the role of glycolysis in diseases, particularly IBD and CRC, via its effects on the intestinal microbiota, immunity, barrier integrity, signaling pathways, transcription factors and some therapeutic strategies targeting glycolytic enzymes.